Public education via the implementation of alternative energy sources in solar water pump - Hamdani*, Hamdani; Myori, Dwiprima Elvanny; Pulungan, Ali Basrah Pulungan (Universitas Lancang Kuning, 2024)
This dedication is underpinned by public insight, and manager Mushalla Darul Ittihad's opinion about alternative energy still needs to be improved. The imbalance between the available electricity and the electricity load used often disrupts electricity due to overload. Interfere with the smoothness of worship activities. Besides lighting and sound amplifiers, the biggest electric charge lies on the water pumps that live all day. Therefore, additional power sources not charging the mushalla's operating costs are needed to cope with the problem. This activity aims to educate participants and offer ideas on the usage of alternative energy in electric water pumps. Implementation method involves observation, design, installation, and education of hybrid systems using solar energy and PLN for water pump energy. The result of the activity is increased knowledge and an installed solar power system for the water pump. The availability of this solar-powered water pump is expected to increase the congregation's participation in the implementation of mashallah activities and better social life.